Moku Hesi Miti Tradition: Birth Ritual in Ethnoparenting of Takpala Indigenous Village Community, Alor Regency - Wollo, Stevanya Lucia Wety; Rachmawati, Yeni; Syaodih, Ernawulan (Journal of Innovation in Educational and Cultural Research, 2026)
This study examines “Moku Hesi Miti," a unique birth ritual of the Abui community in Alor Regency, which holds profound moral, social, and spiritual values but is at risk of being forgotten amid modernisation. This study aims to comprehensively document this tradition and identify its cultural values in child rearing. Using a qualitative phenomenological approach, data were collected through two-stage interviews with an elder of the Takpala traditional community. Findings indicate that “Moku Hesi Miti” fundamentally emphasises the critical role of breast milk as a source of life and sacred blessing, in line with global health recommendations, and highlights the deep connection between physical and spiritual health. This ritual, which involves specific roles for the “Release Tree” and the father, as well as adherence to social taboos, educates children to become strong, independent, and virtuous. This study makes a unique contribution by explaining how this traditional practice strengthens health outcomes and cultural values, offering new perspectives on sociocultural factors in maternal and child health, and enhancing anthropological understanding of social control mechanisms. Ultimately, understanding “Moku Hesi Miti” can serve as the foundation for culturally sensitive public health programs and help preserve local heritage and sustainable ethnic childcare practices.